Evaluation du comportement trophique de Aedes aegypti dans la ville de cotonou au sud du Bénin - Yadouleton Anges; Dramane Gado; Ahadji-Dabla K.M.; Agbanrin Ramziyath; Tchibozo Carine; Agolinou Achaz; Tossou Roland; Baba-Moussa Lamine (European Scientific Journal, ESJ, 2018)
In order to evaluate the trophic behavior of Aedes aegypti in the city of Cotonou, southern Benin, a cross-sectional study was conducted in urban and periurban neighborhoods from April 2016 to August 2017 to collect Ae. Aegypti populations. To achieve this goal, day and night collections, twice a month for one year were done where Ae. Aegypti populations were caught by Human Landing Catch and BG-Sentinel traps. 3,892 Aedes caught by different methods showed that Ae. Aegypti and Ae. circumluteolus are more abundant in urban than peri-urban areas (p<0.05). The aggressive density of Ae. aegypti populations was significantly higher in urban areas (157.43 bites per man per hour) than in peri-urban areas (32.43 bites per man per hour) (p<0.05). Also, out of 250 females blood-fed Ae. Aegypti tested by ELISA (Enzyme Linked Immunosorbent Assay) technique for blood meal identification, 86.80% took their blood meal on humans compared to 4.4% which took their blood meal on sheeps. These findings showed that the city of Cotonou in southern Benin, offered good condition for the development of Ae. aegypti population. The anthropology and endophagy behavior of this mosquito observed through the results of this study is a very favorable clue to vector control strategies based on the use of long-lasting impregnated mosquito nets and insecticide residual sprays adopted in Benin.